ANALISIS KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK MATERI GERAK LURUS DI SMAN 1 SUNGAI RAYA - Nadia, Sovia; Maria S, Haratua Tiur; Habellia, Ray Cinthya (Universitas Tanjungpura, 2023)
This study aims to identify profiles of students' problem-solving abilities and describe the difficulty of solving problems in straight motion material at SMA Negeri 1 Sungai Raya. This research uses a descriptive method. The subjects of this study were 35 students who had studied straight motion material. The data collection instrument used in this study was a solving ability test consisting of 4 essay questions. The results of the study concluded that the problem solving ability of students at SMA Negeri 1 Sungai Raya was still relatively low with a percentage of 38.6%. The results of data analysis are interpreted to mean that 67.2% are categorized as having difficulties. Based on the results of the interviews, students experienced difficulties at stage 1 because they were not used to describing situations in questions, usually directly writing down the quantities that were known and asked. At stage 2 students do not understand the problem so not all quantities are written down. In stage 3, students are confused about determining the formula. For stage 4, students are lacking in arithmetic operations. Then, at the 5th stage. students are not accustomed to making conclusions in working on problems.